Survival improvements in esophageal and gastric cancers in the Nordic countries favor younger patients - Hemminki, Kari; Zitricky, Frantisek; Försti, Asta; Hemminki, Otto; Liska, Vaclav; Hemminki, Akseli (Cancer medicine, 2024)
Esophageal cancer (EC) and gastric cancer (GC) are fatal cancers with a relatively late age of onset. Age is a negative risk factor for survival in many cancers and our aim was to analyze age-specific survival in EC and GC using the recently updated NORDCAN database. NORDCAN data originate from the Danish, Finnish, Norwegian, and Swedish nationwide cancer registries covering years 1972 through 2021 inviting for comparison of 50-year survival trends between the countries. Relative 1- and 5-year survival and 5/1-year conditional survival (i.e., survival in those who were alive in Year 1 to survive additional 4 years) were analyzed. Survival in EC showed large gains for patients below age 80 years, 5-year survival in Norwegian men reaching 30% and in women over 30% but for 80-89 year old survival remained at 10%. In contrast, hardly any gain was seen among the 80-89 year patients for 1-year survival and small gains in 5 year and 5/1-year survival. Survival gaps between age-groups increased over time. For GC there was also a clear age-related negative survival gradient but the survival gaps between the age groups did not widen over time; Norwegian male and female 5-year survival for 80-89 year old was about 20%. The age-specific survival difference in GC arose in Year 1 and did not essentially increase in 5-year survival. While there were differences in survival improvements between the countries, poor survival of the 80-89 year old patients was shared by all of them. To conclude, survival has improved steadily in younger GC and EC patients in most Nordic countries. While the 80-89 year old population accounts for nearly a quarter of all patients and their poor survival depressed overall survival, which can therefore be increased further by improving diagnostics, treatment and care of elderly EC and GC patients.
Keywords: senioři; Stomach Neoplasms; Scandinavian and Nordic Countries; risk factors; senioři nad 80 let; Skandinávie a severské státy; Middle Aged; registrace; mužské pohlaví; stomach cancer; míra přežití; Adult; Registries; věkové faktory; Aged, 80 and over; ženské pohlaví; Humans; Survival Rate; Esophageal Neoplasms; lidé středního věku; Age Factors; treatment; dospělí; relative survival; Female; Aged; mortality; nádory jícnu; lidé; Male; nádory žaludku